The reciprocal interplay of physical activity and health-related quality of life in children and adolescents: evidence for both upward and downward spirals - Groß, Daniel; Schröder, Ines; Wasserfall, Nicola; Eschenbeck, Heike; Kohlmann, Carl-Walter (Applied psychology: health and well-being. Health and well-being, 2023)
OBJECTIVE: This study examines the bidirectional effect between physical activity (PA) and health-related quality of life in children and adolescents, focusing on within-person effects. METHODS: PA and health-related quality of life were assessed in children and adolescents (N = 685, age: M = 10.29 years, SD = 1.35, range = 8-14), via self-report across four waves, each 6 months apart, and a random-intercept cross-lagged panel model with time-invariant cross-lagged effects was calculated. RESULTS: Positive cross-lagged effects between prior PA and health-related quality of life 6 months later ( γ y  = 0.536, 95% CI [0.016, 1.055], p = .043, d = 0.11) and vice versa ( γ x  = 0.015, 95% CI [0.001, 0.030], p = .039, d = 0.12) were found. Furthermore, the random intercept correlation was significant ( T xy  = 3.622, 95% CI [2.204, 5.041], p < .001, d = 0.27). CONCLUSIONS: The findings confirm known correlations between PA and health-related quality of life and extends them by indicating both an upward and downward spiral of PA and health-related quality of life in children and adolescents.
Erstmals veröffentlicht: 20 August 2022
Gesehen am 01.10.2024